Sarah L. McCallum, Elegiac Love and Death in Vergil’s Aeneid, Oxford University Press, 2023. (Stylos, 2024)
En Generic Enrichment in Vergil and Horace (2007), S. Harrison definía el enriquecimiento genérico como “the way in which generically identifiable texts gain literary depth and texture from detailed confrontation with, and consequent inclusion of elements from, texts which appear to belong to other literary genres” (p. 1) y analizaba este fenómeno como particularmente característico de la poesía de Virgilio y Horacio, dado que en sus obras pueden encontrarse “géneros huéspedes” que profundizan la textura del “género anfitrión”.